UNDERSTANDING THE MULTIFACETED DYNAMICS OF GEDSI INTEGRATION IN THE CONTEXT OF INDONESIA'S ENERGY TRANSITION - Loso Judijanto (Prosiding Seminar Nasional Indonesia, 2023)
Gender Equality and Social Inclusion (GEDSI) are pivotal considerations in the global pursuit of sustainable energy transitions. This study delves into the multifaceted dynamics of GEDSI integration in the context of Indonesia's energy transition. The research explores the ethical and strategic imperatives of GEDSI, examining how it addresses historical gender disparities and social inequities while enhancing the energy sector's efficiency and competitiveness. Identifying formidable challenges, including entrenched gender disparities, socio-cultural norms, economic inequalities, and technological disparities, the study emphasizes the need for comprehensive strategies to overcome these barriers. It highlights the opportunities and enablers that can drive GEDSI integration, such as the business case for diversity, technological advancements, capacity building, advocacy, and multisectoral collaboration. The research also underlines the significance of learning from best practices and case studies within Indonesia and internationally to accelerate progress. This study offers valuable insights into Indonesia's journey toward a more inclusive and sustainable energy future, encapsulating dedication, collaboration, and a shared commitment to transform the energy landscape.